l-Arginine and COVID-19: An Update - Ayobami Adebayo (MDPI AG, 2021)
l-Arginine is involved in many different biological processes and recent reports indicate that it could also play a crucial role in the coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Herein, we present an updated systematic overview of the current evidence on the functional contribution of L-Arginine in COVID-19, describing its actions on endothelial cells and the immune system and discussing its potential as a therapeutic tool, emerged from recent clinical experimentations.